GEGAR BUDAYA DAN PERGULATAN IDENTITAS DALAM NOVEL UNE ANNÉE CHEZ LES FRANÇAIS KARYA FOUAD LAROUI - Intan, Tania (Universitas Hasanuddin, 2019)
Cultural shock is a deep and negative response to depression, frustration and disorientation experienced by people who live in a new cultural environment. These psychological and cultural symptoms are experienced by child figures in the novel Une Année chez les Français by Fouad Laroui. Research on cultural shock and identity struggles as a result is carried out by qualitative descriptive methods. Data in the form of relevant citations are collected by referring to the note-taking technique and analyzed to draw conclusions. The results of this study indicate that there are four phases of cultural shock that the main character traverses are: the honeymoon phase, the prison phase, the adaptation phase, and the adjustment phase. The factors that influence the occurrence of cultural shock in these figures are: intrapersonal factors, cultural variations, and socio-political manifestations. The three aspects of the cultural shock that Mehdi experienced were: loss of familiar signs, identity crises, and the breakdown of interpersonal communication that led to frustration and anxiety due to language barriers. While the symptoms of the cultural shock that he experienced were: sadness, loneliness, and misery; behavioral changes, stress or depression, identifying with old cultures or idealizing old regions; loss of identity; not confident; feel deprived, and miss the family.